The Curious Case of the Right to be Forgotten - Bunn, Anna (Elsevier Advanced Technology, 2015)
This paper considers the so-called 'right to be forgotten', in the context of the 2014 decision of the European Court of Justice (ECJ) in the case of Google Spain SL, Google Inc. v Agencia Española de Protección de Datos (AEPD), Mario Costeja González. It also considers the 'right of erasure' contained in the current EU Data Protection Directive, as well as the proposal for a new right of erasure to be included in the new EU data protection framework. The paper proposes a particular way of understanding the right to be forgotten and suggests a broad definition of it. It examines claims that the ECJ's decision in Google 'invented' a right to be forgotten. It also considers whether individuals have a right to be forgotten under the current EU Directive, and whether they will have such a right when the new data protection regulation becomes law. More generally, the paper considers whether a right to be forgotten has been recognised as an aspect of a broader right to privacy, and whether the Google decision moves us closer to an understanding of privacy as the right to an appropriate flow of information, in line with Nissenbaum's framework of contextual integrity.